New Conopid records from the Afrotropical Region (Diptera). Part 1: Paramyopa Kröber, Pseudoconops Camras, Stylogaster Macquart, Thecophora Rondani, and Zodion Latreille - Stuke, Jens-Hermann (Zootaxa, 2015)
New records of 38 species of the Conopid genera Paramyopa Kröber, 1916a, Pseudoconops Camras, 1962b, Stylogaster Macquart, 1835, Thecophora Rondani, 1845, and Zodion Latreille, 1797 are presented from the Afrotropical Region. Stylogaster angolensis spec. nov. (Angola), Stylogaster cryptica spec. nov. (Ethiopia), Stylogaster fianarantsoensis spec. nov. (Madagascar), Stylogaster ivindoensis spec. nov. (Gabon), Stylogaster malaisei spec. nov. (Madagascar), Stylogaster occulta spec. nov. (Democratic Republic of Congo, Burundi), Stylogaster rwenzoriensis spec. nov. (Democratic Republic of Congo), Stylogaster tanzaniensis spec. nov. (Tanzania), Thecophora clementsi spec. nov. (Madagascar), Thecophora freidbergi spec. nov. (Kenya), Thecophora nigrifrons spec. nov. (Kenya, Cameroon), Thecophora obsoleta spec. nov. (Madagascar), and Thecophora submetallica spec. nov. (Madagascar) are new to science. A neotype is designated for Thecophora pilosa (Kröber, 1916). Thecophora africana (Brunetti, 1925), Thecophora flavicornis (Kröber, 1936), and Thecophora ruwenzori (Camras, 1962) are new junior synonyms of Thecophora pilosa; Paramyopa schultzei (Bezzi, 1908) is a new junior synonym of Paramyopa oestracea (Loew, 1863) (syn. nov.). Stylogaster nitidula Kröber, 1936 is interpretated as a nomen dubium (stat. rev.).